2018
DOI: 10.1021/acs.inorgchem.8b00914
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural, Spectral, and Electrochemical Studies of Selenabenziporphyrin and Its Pd(II) Complex

Abstract: A new nonaromatic selenabenziporphyrin was synthesized by (3 + 1) condensation of m-benzitripyrrane and 2,5-bis[( p-tolyl)hydroxymethyl] selenophene under mild trifluoroacetic acid-catalyzed reaction conditions. The selenabenziporphyrin was characterized by high-resolution mass spectrometry, one- and two-dimensional NMR spectroscopy, and X-ray crystallography. The crystal structure revealed that the macrocycle was planar with moderately tilted m-phenylene ring and that the phenylene ring completely blocks the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…Comparison of 1 H NMR spectra of fused selena benziporphyrin 1b with that of our recently reported nonaromatic selena m -benziporphyrin I·Se (Figure S20 and Table S1) clearly supports the antiaromatic nature of macrocycle 1b . For example, the inner CH proton (type k) in selena m -benziporphyrin I·Se appeared at 7.20 ppm, whereas the same proton in macrocycle 1b was downfield shifted and appeared at 11.30 ppm.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Comparison of 1 H NMR spectra of fused selena benziporphyrin 1b with that of our recently reported nonaromatic selena m -benziporphyrin I·Se (Figure S20 and Table S1) clearly supports the antiaromatic nature of macrocycle 1b . For example, the inner CH proton (type k) in selena m -benziporphyrin I·Se appeared at 7.20 ppm, whereas the same proton in macrocycle 1b was downfield shifted and appeared at 11.30 ppm.…”
supporting
confidence: 75%
“…Monobenziporphyrins result from replacement of one of the pyrrole rings of tetrapyrrolic porphyrin with a benzene ring. , There are two possible monobenziporphyrins depending on the linking of pyrrole rings with benzene rings via meso -carbon bridges in benziporphyrinoid systems: meta -benziporphyrins , I , in which the pyrrole rings are connected at 1,3-positions of the benzene ring, and para -benziporphyrins II , in which the pyrrole rings are connected at 1,4-positions of the benzene ring (Figure ). The extensive studies indicated that m -benziporphyrins I are nonaromatic, whereas p -benziporphyrins are aromatic. The complete nonaromatic nature of m -benziporphyrins was attributed to retaining the strong 6π arene aromaticity of the benzene ring relative to the porphyrinoid aromaticity. Over the years, extensive research has been carried out by Lash et al ,, and other research groups and showed that by introducing suitable substituent(s) on the benzene ring of m -benziporphyrins, these macrocycles can be transformed into aromatic compounds . For example, the suitably placed hydroxyl group on the benzene ring of m -benziporphyrins such as compound III led to the aromaticity of m -benziporphyrins due to keto–enol tautomerism. ,,, Alternately, the nonaromaticity of m -benziporphyrins can be altered by replacing the m -phenylene ring with a fused aromatic groups such as naphthalene, anthracene, pyrene, etc., (premodification approach) to result in meso -fused carbaporphyrins such as IV , found to be aromatic.…”
mentioning
confidence: 99%
“…In this respect, carbaporphyrinoids incorporating phenylene rings, , namely, m -benziporphyrins 1-X , oxy- m -benziporphyrins, , and p -benziporphyrins 2-X , , were found particularly alluring, giving an access to complexes with metal···arene π, and σ bonds (Figure ). Benziporphyrins demonstrated formation of coordination compounds with variety of metals, metalloids, and nonmetals. Moreover, in cases of palladium­(II), rhodium­(III), and gold­(III) , complexes of 1-NH and 2-NH the metal···π interactions were envisaged to be stimuli of unusual reactivity resulting in the contraction of benzene unit to cyclopentadiene, leading eventually to complexes of 21-carbaporphyrins.…”
mentioning
confidence: 99%
“…Replacement of the m -phenylene subunit of 1-X with the 2,7-naphthalenyl moiety in 13-X clearly influenced the potential coordination properties of the macrocycle. First, the modification distinctively increased dimensions of the coordination pocket, as illustrated by the growing distance between nitrogen atoms of opposite pyrroles from 4.72 Å ( 1-Se ) to 5.62 Å ( 13-Se ) and 5.74 Å ( 13-Te ). This clearly affected possible conformational dynamics, e.g., allowing for subunit rotations.…”
mentioning
confidence: 99%
“…The electronic properties of m - and p -benziporphyrins can be altered further by replacing one of the pyrrole rings that is across the phenylene subunit of benziporphyrins by other five-membered heterocyclic such as thiophene, furan, selenophene, and tellurophene, and the resulting core-modified benziporphyrins or hetero benziporphyrins with N 2 C 2 X (X = S, O, Se, and Te) cores are expected to exhibit different physicochemical and coordination properties compared to benziporphyrins with a N 3 C 2 core. ,,, A perusal of literature revealed that the all core-modified derivatives of aromatic p -benziporphyrins have not been synthesized, and no systematic investigation of the effect of core modification on electronic properties of p -benziporphyrins has been investigated. Herein, we report the synthesis of the missing hetero p -benziporphyrins such as Selena p -benziporphyrin 5 and tellura p -benziporphyrin 6 by adopting a 3 + 1 synthetic strategy (Chart ).…”
Section: Introductionmentioning
confidence: 99%